1999
DOI: 10.1128/aem.65.6.2396-2401.1999
|View full text |Cite
|
Sign up to set email alerts
|

Lethality of a Heat- and Phosphate-Catalyzed Glucose By-Product to Escherichia coli O157:H7 and Partial Protection Conferred by the rpoS Regulon

Abstract: A by-product of glucose produced during sterilization (121°C, 15 lb/in2, 15 min) at neutral pH and in the presence of phosphate (i.e., phosphate-buffered saline) was bactericidal toEscherichia coli O157:H7 (ATCC 43895). Other six-carbon (fructose and galactose) and five-carbon (arabinose, ribose, and xylose) reducing sugars also produced a toxic by-product under the same conditions. Fructose and the five-carbon sugars yielded the most bactericidal activity. Glucose concentrations of 1% (wt/vol) resulted in a 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…There are studies showing interactions of phosphate with sugar in chemical reactions. For example, it has been found that sugar solutions became bactericidal after being heated in the presence of phosphate , . Recent studies , have shown that when sugars and ascorbic acid were heated in the presence of phosphate (without realizing the phosphate effect), many compounds besides furan were produced including acetic acid, formic acid, acetaldehyde, and glycolaldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…There are studies showing interactions of phosphate with sugar in chemical reactions. For example, it has been found that sugar solutions became bactericidal after being heated in the presence of phosphate , . Recent studies , have shown that when sugars and ascorbic acid were heated in the presence of phosphate (without realizing the phosphate effect), many compounds besides furan were produced including acetic acid, formic acid, acetaldehyde, and glycolaldehyde.…”
Section: Resultsmentioning
confidence: 99%